IMPACT OF THE DAMPER CHARACTERISTICS ON THE BEHAVIOR OF SUSPENSION SYSTEM AND THE WHOLE VEHICLЕ - Maljković, Miloš; Blagojević, Ivan; Popović, Vladimir; Stamenković, Dragan (Journal of Applied Engineering Science, 2018)
Damper asymmetry is a phenomenon for which there is no confi rmed explanation in the literature, although it is present in almost all variants of telescopic dampers. This paper analyzes the infl uence of various characteristics of dampers, both symmetrical and asymmetrical, on the behavior of the suspension system and the whole vehicle. Different tests have been carried out, and they simulate the different types of vehicle movement that are present in exploitation. The simulation was performed in CarSim 8 software package for the vehicle with chosen characteristics. Appropriate conclusions were drawn on the basis of the conducted research, i.e. the differences in the behavior of the suspension system and the vehicle depending on the selected characteristics of the damper are shown.